2020
DOI: 10.1002/ejp.1631
|View full text |Cite
|
Sign up to set email alerts
|

Movement, posture and low back pain. How do they relate? A replicated single‐case design in 12 people with persistent, disabling low back pain

Abstract: Background Movement and posture are commonly believed to relate to non‐specific low back pain (NSLBP). While people with NSLBP appear to move and posture themselves differently from those without NSLBP, changes in movement and posture infrequently relate to improvements in NSLBP when analysed at a group‐level. Additionally, little is known about how movement or posture change when clinical outcome improves. Methods Within‐person relationships were investigated using a replicated, repeated measures, single‐case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
0
24
0
3
Order By: Relevance
“…For clinicians managing people with LBP related to lifting, advising them to adopt more squat-like lifting techniques in order to reduce the risk of LBP or manage it lacks evidence. Recent research supports that recovery from chronic and disabling LBP is associated with movement patterns that society perceives to be less safe (a more flexed lumbar spine and faster movement speed) [45]. The lack of clear associations with lifting biomechanics and pain intensity during repeated lifting in this study, suggests a range of factors across biopsychosocial domains should be explored to best assist those with lifting-related LBP [73,74].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For clinicians managing people with LBP related to lifting, advising them to adopt more squat-like lifting techniques in order to reduce the risk of LBP or manage it lacks evidence. Recent research supports that recovery from chronic and disabling LBP is associated with movement patterns that society perceives to be less safe (a more flexed lumbar spine and faster movement speed) [45]. The lack of clear associations with lifting biomechanics and pain intensity during repeated lifting in this study, suggests a range of factors across biopsychosocial domains should be explored to best assist those with lifting-related LBP [73,74].…”
Section: Discussionmentioning
confidence: 68%
“…Although this cross-sectional study cannot determine the cause-effect relationship of LBP related to lifting, or the reason for the differences seen in lifting technique, previous research has demonstrated that people both with LBP [42,43] and without LBP [44], who have higher levels of pain-related fear, lift with less lumbar flexion. There is also evidence that as people with chronic LBP improve, how they perform activities such as bending and lifting becomes faster with greater lumbar ROM in most cases [45]. Together this work suggests that people with LBP perceive squat-like lifting to be 'protective' during bending and lifting and therefore move accordingly.…”
Section: Aim 1 -Comparison Of Lifting Technique Between Lbp and Nolbp Groupsmentioning
confidence: 80%
“…Therefore, although this study showed a redundancy among the tasks, it is possible that some functional tasks may be more sensitive, for example with respect to pain intensity or pain-related fear. In this regard, some authors suggested that selecting a specific task for each individual based on their identified limitations could be helpful when analyzing the relationships between spinal movement and patient-related outcomes ( Wernli et al, 2020a ). It is currently unknown if selecting one sagittal-plane task based on the individual limitation would be more appropriate to analyze such relationships and future studies should address this gap.…”
Section: Discussionmentioning
confidence: 99%
“…Además, la relación causal entre las posturas de la columna vertebral y el dolor lumbar carece de consenso. [29][30][31][32] Es interesante resaltar que investigaciones previas han demostrado que aquellos que creen que levantar con la espalda recta es más seguro, puntuaron más alto en el Back-PAQ que aquellos que eligen una espalda redondeada. 15,17 Las creencias protectoras alrededor de la espalda fueron altamente prevalentes.…”
Section: íTems Individualesunclassified